Efficacy and safety of two doses of budesonide/formoterol fumarate metered dose inhaler in COPD. Issue 2 (27th April 2020) - Hanania, Nicola A.; Papi, Alberto; Anzueto, Antonio; Martinez, Fernando J.; Rossman, Kimberly A.; Cappelletti, Christy S.; Duncan, Elizabeth A.; Nyberg, Jack S.; Dorinsky, Paul M.
Inhaled corticosteroid/long-acting β2 -agonist combination therapy is a recommended treatment option for patients with chronic obstructive pulmonary disease (COPD) and increased exacerbation risk, particularly those with elevated blood eosinophil levels. SOPHOS (NCT02727660) evaluated the efficacy and safety of two doses of budesonide/formoterol fumarate dihydrate metered dose inhaler (BFF MDI) versus formoterol fumarate dihydrate (FF) MDI, each delivered using co-suspension delivery technology, in patients with moderate-to-very severe COPD and a history of exacerbations. In this phase 3, randomised, double-blind, parallel-group, 12–52-week, variable length study, patients received twice-daily BFF MDI 320/10 µg or 160/10 µg, or FF MDI 10 µg. The primary endpoint was change from baseline in morning pre-dose trough forced expiratory volume in 1 s (FEV1 ) at week 12. Secondary and other endpoints included assessments of moderate/severe COPD exacerbations and safety. The primary analysis (modified intent-to-treat) population included 1843 patients (BFF MDI 320/10 µg, n=619; BFF MDI 160/10 µg, n=617; and FF MDI, n=607). BFF MDI 320/10 µg and 160/10 µg improved morning pre-dose trough FEV1 at week 12 versus FF MDI (least squares mean differences 34 mL [p=0.0081] and 32 mL [p=0.0134], respectively), increased time to first exacerbation (hazard ratios 0.827 [p=0.0441] and 0.803 [p=0.0198], respectively) and reduced exacerbation rate (rate ratios 0.67 [p=0.0001] and 0.71 [p=0.0010], respectively). Lung function and exacerbation benefits were driven by patients with blood eosinophil counts ≥150 cells·mm −3 . The incidence of adverse events was similar, and pneumonia rates were low (≤2.4%) across treatments. SOPHOS demonstrated the efficacy and tolerability of BFF MDI 320/10 µg and 160/10 µg in patients with moderate-to-very severe COPD at increased risk of exacerbations. Co-suspension delivery technology budesonide/formoterol fumarate metered dose inhaler improve lung function and reduce exacerbation risk versus LABA monotherapy in patients with moderate to very severe COPD and an exacerbation history in the prior year http://bit.ly/3aDOvru